ANALISIS DETERMINAN AUDITOR INTERNAL PADA EFEKTIVITAS AUDIT INTERNAL SEKTOR PUBLIK (STUDI PADA INSPEKTORAT PROVINSI DKI JAKARTA) - Christopher Septian Nainggolan; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
This research was conducted with the aim of examining the competence of internal auditors, the support of the auditee, the independence of internal auditors, and the relationship between internal auditors and external auditors in their influence on the effectiveness of internal audits. The population in this study are the internal auditors of DKI Jakarta Provincial Inspectorate which totalling 77 peoples. The sampling method in this study is using convenience sampling. Based from the total population, as many as 55 respondents were willing to become samples in this study. Research data were obtained by giving questionnaires to the respondents. The research hypothesis were tested using multiple regression analysis. The results of the study indicate that auditor competence and the relationship of internal auditors with external auditors have a positive and significant influence on the effectiveness of internal audits, whereas auditor independence and auditee support have no effect on the effectiveness of internal audits.